Development of an Android-Based Educational Game to Introduce Sumbawa's Art and Culture to Elementary School Students - Attaqwa, M.Aswin Syarif; Hammad, Rifqi; Sujaka, Tomi Tri (Politeknik Negeri Lhokseumawe, 2025)
Technology is increasingly being used to facilitate work in various fields, including education. One of the uses of technology in education is as a learning medium. However, the use of learning media, especially technology-based media, is still very limited. This affects the learning process, where children often become easily bored due to a lack of interest in studying. Therefore, based on this issue, the researcher developed an Android-based educational game to help children learn about the art and culture of Sumbawa, specifically Satera Jontal (Sumbawa script) and traditional ceremonies of the Sumbawa region. This study uses the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. Based on the results of media expert validation, a score of 92% was obtained; material expert validation scored 95%; and user testing produced a result of 82%. These results indicate that the developed Android-based educational game is suitable for use. Based on pretest results from users, the average score was 56.36, while the posttest results showed an average score of 74.24. These results demonstrate that the developed educational game can improve student learning outcomes